PHYTOCHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITIES OF CRUDE EXTRACT FROM FLOWERS AND LEAVES OF Rhododendron arboreum Sm. FROM NORTHERN THAILAND - WINITCHA, SUPANIDA; LIENGPRAYOON, SIRILUCK; SUPHAMITMONGKOL, WARAWUT; TOMORN, NADDAMAS; CHAIYUT, JATUPORN; LERKSAMRAN, TUKSIN; BANCHONG, YUTTHANA; TRISONTHI, PIYAPAT; SAAH, SAFIAH; MUSIGAMART, NATEDAO (Malaysian Applied Biology, 2021)
Rhododendron arboreum Sm. has wide applications in food and beverage, medicines, and cosmetics because the plant contains bioactive phytochemical components. In Thailand, other than for horticultural purposes, scant literature describes the potential applications of this Rhododendron species. Phytochemical composition, biological activity, and cell cytotoxicity of R. arboreum Sm. flower petal and leaf extracts were determined. Ethanolic extracts of fresh and dried flower petals (FF and DF, respectively) and dried leaves (DL) of R. arboreum were prepared by maceration with 60% ethanol for 7 days. Extraction yields of both FF and DF were higher than DL (19.22, 16.76, and 8.50% for FF, DF, and DL, respectively). Preliminary qualitative phytochemical screening showed different compositions in diverse plant parts. Saponins and tannins were present in every extract, with anthraquinones detected only in flowers and terpenoids only in leaves. Total phenolic (TPC) and flavonoid contents (TFC) were highest in DL (405.21 mg gallic acid equivalent and 127.30 mg catechin equivalent per g of dry extract, respectively), followed by DF and FF. Antioxidant properties were determined using two radical scavenging assays as 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis(3-ethyl-benzthiazoline-6-sulfonic acid (ABTS). Results indicated that all extracts exhibited better inhibitory activity against DPPH radical than ABTS radical as evidenced by lower IC50 range 24.65-48.15 ìg/mL for DPPH and 65.19-76.36 ìg/mL for ABTS, respectively. A positive correlation coefficient between the two antioxidant assays and TPC and TFC of Rhododendron extracts indicated antioxidant potential distributed in both components. No cytotoxicity was recorded in the three extracts, with concentrations less than 500 μg/mL for both 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide (MTT) and CellTiter-Blue® assay. In vitro studies exhibited dose-dependent and strong anti-melanogenic and anti-inflammatory activities ranging from 50 to 250 μg/mL for FF, DF, and DL. Results identified various bioactive constituents with potential biological activity (antioxidant, antiinflammatory, and anti-melanogenic), while non-cytotoxicity in R. arboreum flower and leaf extracts suggested the possibility of further applications as a functional ingredient in cosmetics.